Implementasi Akad Murabahah: Peningkatan Kompetensi Pelaku Usaha Kredit Syariah - Ferry Diyanti; Muhammad Iqbal (CV. Multi Kreasi Media, 2025)
The improvement in living standards of the Samarinda community has increased the demand for safe and sharia-compliant financing alternatives, particularly murabahah-based financing. Although sharia credit business actors have implemented murabahah contracts, evaluations of their accounting practices have not been previously conducted. This Community Service Program (PKM) aims to evaluate the implementation of murabahah accounting practices through discussion and knowledge-sharing activities with sharia credit business actors. The methods include object mapping, material preparation, interactive discussions, and activity evaluation using participant satisfaction questionnaires. The results indicate that murabahah transactions have generally complied with sharia principles; however, improvements are needed in accounting treatment to enhance transparency and accountability in financial reporting. This program provides positive social and economic impacts, strengthens the understanding of murabahah accounting practices among business actors, and enhances public trust in sharia-based credit transactions.